Morphological Differences in the Aorto-iliac Segment in AAA Patients of Caucasian and Asian Origin. Issue 6 (June 2016) - Banzic, I.; Lu, Q.; Zhang, L.; Stepak, H.; Davidovic, L.; Oszkinis, G.; Mladenovic, A.; Markovic, M.; Rancic, Z.; Jing, Z.; Brankovic, M.
Abstract : Objective: The objective was to quantify aorto-iliac morphology differences between AAA patients of Caucasian and Asian origin. Additionally, the impact of patient demographic characteristics was assessed, which could influence the morphological differences. Methods: This international multicentre study included two tertiary referral institutions from Europe and one from China. CT scans with 3D reconstruction of 296 patients with infrarenal AAA >5 cm were analysed. Eighteen measurements were recorded from each CT scan and compared between Caucasian and Asian patients. Results: Caucasian patients had longer common iliac arteries (right: 65.0 vs. 33.1 mm, p  < .001 left: 65.0 vs. 35.2 mm, p  < .001), longer aneurysm neck (33.0 vs. 28.4 mm, p  < .001), greater aneurysm to aortic axis angle (153.0° vs. 142.2°, p  < .001), and longer combined aorto-iliac length (195.7 vs. 189.2 mm, p  < .001). However, Asian patients had a longer infrarenal abdominal aorta (152.0 vs. 130.0 mm, p  < .001), longer AAA (126.2 vs. 93.0 mm), and greater linear distance from renal artery to aorto-iliac bifurcation (143.6 vs. 116.0 mm, p  < .001). Caucasian patients had a larger inner common iliac artery diameter (right: 16.0 vs. 14.9 mm, p  < .001, left: 16.0 vs. 15.2 mm, p  < .001), larger inner exernal iliac artery diameter (right: 9.0 vs. 7.5 mm, p  < .001 left: 9.0 vs. 7.7 mm, p  < .001), and larger inner common femoral artery diameter (right: 10.0 vs. 5.9 mm, p  < .001 left: 10.0 vs. 6.1 mm, p  < .001). No difference was observed in AAA transverse diameter (62.0 vs. 63.1 mm, p  = .492). Conclusion: The results showed that aorto-iliac anatomy in Caucasians differs significantly from Asians, particularly in the length of the common iliac arteries and infrarenal abdominal aorta, and in the transverse diameter of the common, external iliac, and common femoral arteries. Therefore, the exact criteria for stent graft design are dependent on the racial origin of the patient.